An Exponential Regression Model Reveals the Continuous Development of B Cell Subpopulations Used as Reference Values in Children - Königs, Christoph; Schultze-Strasser, Stephan; Quaiser, Andrea; Bochennek, Konrad; Schwabe, Dirk; Klingebiel, Thomas E.; Koehl, Ulrike; Cappel, Claudia; Rolle, Udo; Bader, Peter; Bremm, Melanie; Huenecke, Sabine; et al. (Frontiers in Pediatrics, 2018)
B lymphocytes are key players in humoral immunity, expressing diverse surface immunoglobulin receptors directed against specific antigenic epitopes. The development and profile of distinct subpopulations have gained awareness in the setting of primary immunodeficiency disorders, primary or secondary autoimmunity and as therapeutic targets of specific antibodies in various diseases. The major B cell subpopulations in peripheral blood include naïve (CD19+ or CD20+IgD+CD27−), non-switched memory (CD19+ or CD20+IgD+CD27+) and switched memory B cells (CD19+ or CD20+IgD−CD27+). Furthermore, less common B cell subpopulations have also been described as having a role in the suppressive capacity of B cells to maintain self-tolerance. Data on reference values for B cell subpopulations are limited and only available for older age groups, neglecting the continuous process of human B cell development in children and adolescents. This study was designed to establish an exponential regression model to produce continuous reference values for main B cell subpopulations to reflect the dynamic maturation of the human immune system in healthy children.